Transparent UWB Antenna with IZTO/Ag/IZTO Multilayer Electrode Film - Seungman Hong; Youngsung Kim; Chang Won Jung (International Journal of Antennas and Propagation)
Ultra-wide band (UWB) antennas with transparent indium zinc tin oxide (IZTO)/Ag/IZTO multilayer electrode films are presented. The geometry of the radiator of the proposed UWB antenna is a simple semicircular shape, and acryl is used for the transparent substrate. Three types of proposed antennas are used for the comparison: first, an UWB antenna with a copper sheet only (CUWB); second, a transparent UWB antenna with a transparent radiator only (TRUWB); and, third, an entirely transparent UWB antenna (TUWB). The IZTO/Ag/IZTO multilayer electrode is fabricated by a physical vapor deposition process in the highly maintained vacuum. The transmittance of the multilayer film at 550 nm wavelength is over 80%, and the conductivity is 3,960,000 S/m. The proposed CUWB, TRUWB, and TUWB have peak gains of 4.17, 3.14, and 0.74 dBi and radiation efficiency levels of 84.8, 64.5, and 42.1% at the center frequency of UWB service (6.5 GHz), respectively.